Islamic Principles For Religious Harmony - Mohamed Mihlar Abdul Muthaliff (Akidah and Religion Studies Programme ,Faculty of Leadership and Management, USIM, 2024)
E-Proceedings Of The International Conference On Aqidah, Religions And Social Sciences (SIGMA10) “ Towards Peaceful Co-Existence And Excellence Of Ummah : An Implication Of Rahmatan Lil’Alamin” Organized by: Akidah and Religion Studies Programme, Faculty of Leadership and Management 4th November 2020. Editors: Mohd Radhi Ibrahim, Wan Mohd Fazrul Azdi Wan Razali, Rosidayu Sabran, Nik Suhaida Nik Abdul Majid, Najib Sheikh Abdisamad, Mohd Hamidi Ismail, Yuseri Ahmad